Răspuns :
(2x+5)(2x-3)-(x-2)(x-3)-(3x-2)(2x+5) =
Inmultesti parantezele
= 4x² - 6x + 10x - 15 -( x² -3x-2x+6)-(6x²+15x-4x-10 ) =
Reduci termenii asemenea
= 4x² - 6x + 10x - 15 - ( x² - 5x + 6 ) - (6x² + 11x - 10 ) =
= - 3x² - 6x + 10x - 15 + 5x - 6-11x + 10 =
= -3x² - 2x - 15 - 6 + 10 =
= -3x² - 2x - 11
Inmultesti parantezele
= 4x² - 6x + 10x - 15 -( x² -3x-2x+6)-(6x²+15x-4x-10 ) =
Reduci termenii asemenea
= 4x² - 6x + 10x - 15 - ( x² - 5x + 6 ) - (6x² + 11x - 10 ) =
= - 3x² - 6x + 10x - 15 + 5x - 6-11x + 10 =
= -3x² - 2x - 15 - 6 + 10 =
= -3x² - 2x - 11